Effects of total crop straw return on soil fertility and field ecological environment - HONG Chun-lai; WEI You-zhang; HUANG Jin-fa; WANG Run-yi; YANG Xiao-e (浙江大学学报. 农业与生命科学版, 2003)
Two years field experiments on application of total crop straw return were carried out. Results showed that rice tillering and barley seeding ratio was not apparently influenced by application of total crop straw return combined with normal fertilization. The level of soil fertility was increased, the organic matter content was increased from the previous 4.23% to 4.38%, readily available P and K from 83 mg/kg and 6.9 mg/kg to 110.2 mg/kg and 11.7 mg/kg respectively, total nitrogen from 0.205% to 0.229%, whereas the net increase of available nitrogen was 25.5 mg/kg. Field ecological environment was considerably improved. Weed incidence rate was decreased by 2/3 or so. In winter, the gap between maximum temperature to minimum temperature in 0-20 cm depth of soil was lessened effectively. Under the condition of total crop straw return treatment the minimum soil temperature was 1-2.5℃ higher than that of the control and the maximum temperature was 1-3℃ lower. The water content in silt loam soil for the total crop straw return treatment was 1.5%-3% higher than that for the control. The crop yield was enhanced by application of total crop straw return.